Obesity treatment - overview of pharmacological and surgical methods - Osiak, Joanna; Mikut, Karolina; Wijata, Aleksandra; Kędziora-Kornatowska, Kornelia (Journal of Education, Health and Sport, 2022)
Introduction and purpose of the work: Obesity is a chronic disease that leads to many complications. Almost a third of the world’s population is now classified as overweight or obese. This is a huge global problem. The base of treatment is diet and physical activity, but fortunately nowadays we also have pharmacological and surgical treatment - which are increasingly used. The aim of this study is to draw attention to obesity disease which may lead to serious complications and compare available pharmacological and surgical treatment. State of knowledge (brief description): Treating obesity is a difficult and often multidisciplinary challenge. Currently many drugs with different mechanisms and different efficiencies has been approved for treatment. All of them show efficiency, but the available studies show that surgical treatment produces better results than pharmacological treatment. Summary: We currently have a huge range of obesity treatment options available. Surgical treatment produces better results than pharmacological treatment. Nevertheless, not every patient qualifies for bariatric surgery. Pharmacological methods are also effective. The treatment method should be individually selected for the patient.